Wilsonian renormalization of noncommutative scalar field theory - Gurǎu, Rǎzvan; Rosten, Oliver J. (Journal of high energy physics, 2009)
Drawing on analogies with the commutative case, the Wilsonian picture of renormalization is developed for noncommutative scalar field theory. The dimensionful noncommutativity parameter, θ, induces several new features. Fixed-points are replaced by `floating-points' (actions which are scale independent only up to appearances of θ written in cutoff units). Furthermore, it is found that one must use correctly normalized operators, with respect to a new scalar product, to define the right notion of relevance and irrelevance. In this framework it is straightforward and intuitive to reproduce the classification of operators found by Grosse & Wulkenhaar, around the Gaussian floating-point. The one-loop β-function of their model is computed directly within the exact renormalization group, reproducing the previous result that it vanishes in the self-dual theory, in the limit of large cutoff. With the link between this methodology and earlier results made, it is discussed how the vanishing of the β-function to all loops, as found by Disertori et al., should be interpreted in a Wilsonian framework.